Epilepsy, impaired functioning, and quality of life in patients with tuberous sclerosis complex. Issue 4 (27th October 2019) - Vergeer, Menno; de Ranitz‐Greven, Wendela L.; Neary, Maureen P.; Ionescu‐Ittu, Raluca; Emond, Bruno; Sheng Duh, Mei; Jansen, Floor; Zonnenberg, Bernard A.
Abstract: Objective: To estimate health‐related quality of life (HRQoL) in patients with tuberous sclerosis complex (TSC) and associated manifestations and to identify potential factors associated with HRQoL in this population of patients. Methods: We performed a retrospective chart review of adults with TSC who attended the outpatient clinic of the University Medical Center Utrecht in the Netherlands from 1990 to 2015 (N = 363; on average 33.6 years of follow‐up). HRQoL data were assessed in 2012 using the Health Utility Index version 3 (HUI‐3) questionnaire completed by patients or caregivers (N = 214 with HUI score and ≥1 TSC manifestation, including renal angiomyolipomas [rAMLs], subependymal giant cell astrocytoma [SEGA], or epilepsy). Results: Of 214 patients in the study sample, 171 had TSC‐associated epilepsy (with or without rAML/SEGA), 37 had TSC and rAML (without epilepsy or SEGA), and 6 had other combinations of manifestations. The median HUI score for the 214 patients with ≥1 TSC manifestation was 0.51 (−0.371 to 1 scale, 1 = perfect health, 0 = death, <0 = worse than death). Among all components used to build the overall HUI score, the cognition component had the lowest score (mean = 0.47; 0‐1 scale). Patients with TSC‐epilepsy had significantly lower overall HUI than patients with TSC and rAML only (median HUI = 0.31 vs 0.95, P < .05), especially those who were in refractory state for prolonged periods of time (median HUI = −0.11 among patients with seizures during the entire duration of their follow‐up time). In multivariate analyses, severe impairment of daily functioning was the strongest predictor of HRQoL decrement (adjusted HUI difference between patients with severe vs. no impairment = −0.55, P < .05). Significance: This study showed that TSC‐related epilepsy is associated with lower HUI, especially for patients who have refractory seizures for prolonged periods of time. Early and effective interventions to control or reduce seizures and preserve patients' cognitive functions may help to improve patients' quality of life.